THE INFLUENCE OF PROMOTION, SERVICE QUALITY AND PRODUCT QUALITY ON PURCHASE DECISIONS AT KARUNGJANTAN - Gustini, Ni Ketut; Setiawani, Putu Amanda; Ferdiana Sari, Putu Anastasya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study analyzes the influence of promotion, service quality, and product quality on consumer purchase decisions at Karungjantan Store. The research was motivated by a decline in sales performance, which is presumed to be caused by ineffective promotional strategies, inconsistent service delivery, and unsatisfactory product quality. A quantitative method was employed, involving a survey of 100 consumers selected through purposive sampling. The data were analyzed using multiple linear regression to determine both the simultaneous and partial effects of the independent variables on purchase decisions. The results reveal that promotion, service quality, and product quality simultaneously have a significant influence on purchase decisions. Partially, promotion and product quality have a positive and significant impact, whereas service quality does not show a significant effect. These findings suggest that the management of Karungjantan Store should optimize their promotional efforts across various platforms, improve service delivery through staff training, and maintain consistent product quality to enhance consumer satisfaction and encourage purchasing behavior.